Quantification of the likelihood of single event multiple transients in logic circuits in bulk CMOS technology. (February 2018) - Rao, Nanditha P.; Desai, Madhav P.
Abstract: It is well known that high-energy particle strikes on an integrated circuit can cause circuit errors. We quantify the fraction of a layout which is susceptible to multiple transients, through the notion of critical area fraction (CAF). We perform a 2D-study on a layout of 65 nm planar transistors to evaluate maximum values of CAF. We find that CAF can be as high as 1, that is, 100% of the layout area is vulnerable. Potentials of adjacent source/drain regions play a significant role in increasing the CAF and simple layout techniques do not reduce the CAF substantially. We confirm these observations through 3D simulations of inverter layouts. A key observation is that, CAF is high in the region of the layout which contains small gates. At the circuit-level, multiple transients not only cause multiple errors, they also merge to create wider transient increasing its capture probability. A circuit-aware placement of vulnerable gates and alternate latch designs may be required to alleviate the problem.